Sustainable practices and their impact on the operations of fresh fruits and vegetables market in the cold chain - Nada Jabbour Al Maalouf; Jean Elia; Fawzi Boutros; Mohammad Balouza; Chadia Sawaya (Cleaner Logistics and Supply Chain)
This study’s main goal was to investigate the effects of sustainable practices on the operational performance of fresh products within Lebanon’s cold chain in terms of operational flexibility, product delivery, quality, and cost. This explanatory research employs a positivist philosophy, logical reasoning, a questionnaire, and a quantitative single-method approach to investigate the research hypotheses. The managers in charge of Lebanon-based businesses that run a cold supply chain for fruits and vegetables made up the target population. A sample of 136 managers filled out the survey. The results revealed a strong positive relationship between sustainable supply chain practices and operational flexibility, product quality, delivery, and cost. Due to their significant influence on operational performance, sustainable supply chain management practices are strongly advised for Lebanese businesses operating in the fruits and vegetables sector. Firms can improve their operational performance while incorporating sustainable practices all along their supply chain. These practices hold accountable all parties concerned with the production and distribution of food in Lebanon. This study contributes to the existing literature by providing empirical evidence on the impact of sustainable practices specifically within the Lebanese cold chain for fresh fruits and vegetables, highlighting its originality in addressing a gap in research on this critical sector.